Engineered CaCO3 nanoparticles with targeting activity: A simple approach for a vascular intended drug delivery system. (29th May 2017) - Ferrari, Pier Francesco; Aliakbarian, Bahar; Zattera, Elena; Pastorino, Laura; Palombo, Domenico; Perego, Patrizia
Abstract: During the last decade, great attention has been paid to drug delivery systems that are able to induce a site‐specific and tunable release of biomolecules, attenuating the drawbacks of common therapy. The encapsulation of bioactive compounds, such as proteins and drugs, offers the advantage of enhancing the pharmacokinetics and bioavaliability of the entrapped molecules. The encapsulating technique and coating agents are chosen on the basis of the desired functionality of the final product, release kinetics, and fabrication costs. Calcium carbonate (CaCO3 ) is considered an ideal substrate to fabricate particles at the nanoscale level. In this work, CaCO3 nanoparticles were synthesized through a two‐step protocol which comprised complex coacervation and mineralization, and they were loaded with bovine serum albumin (BSA) as a model protein. The synthesized nanoparticles were then functionalized with the layer‐by‐layer (LbL) electrostatic self‐assembling technique using chitosan as a polycation and dextran sulphate as a polyanion. The multilayered architecture that covers CaCO3 nanoparticles prevented a burst release of BSA, resulting in 77.34 ± 1.22 % of the released protein, after 72 h of incubation. A horseradish peroxidase‐linked IgG was immobilized at the outer particle layer and its presence was detected via chemiluminescence. Multilayered and non‐multilayered nanoparticles were biocompatible until 7 days using EA. hy926 endothelial cells. Here, we report a cost‐effective protocol to obtain protein‐loaded CaCO3 nanoparticles (diameter < 155 nm) using a coacervate‐based synthesis system. Furthermore, with a very simple technique these nanoparticles were functionalized with antibodies, developing immuno‐nanoparticles to apply in the drug delivery field.